Post a New Question

math

posted by .

3x^(1/3) + 2x^(2/3) = 5
solve for x

  • math -

    Use the substitution
    u=x(1/3)
    The original equation
    3x^(1/3) + 2x^(2/3) = 5
    now becomes
    3u + 2u² = 5
    Solve by the quadratic formula for u, and finally replace u by x(1/3).

  • math -

    Sorry, (1/3) should read (1/3)

  • math -

    I'll try it again:
    x(1/3) should read x(1/3)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question